PERANAN KECERDASAN EMOSI, KEPUASAN KERJA DAN KEPEMIMPINAN TRANSFORMASIONAL TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR PERAWAT - , DEWI MASRUROH ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The rapid development of hospital industry cause business competition in term of hospital service become very hostile. Therefore, nurses are demanded to perform organizational citizenship behavior (OCB), because of OCB support organization effectiveness. Several researches found that emotional intelligence, job satisfaction and transformational leadership have predicted OCB. In this study, research objective was to examine that emotional intelligence, job satisfaction and transformational leadership have predicted to nursesâ organizational citizenship behavior (OCB). Hypothesis that researcher proposed in this study was emotional intelligence, job satisfaction and transformational leadership altogether were predictors of nursesâ OCB. This study was a field research that implemented a quantative methodology by means of questionnaire as data collecting tools. Questionnaire that researcher implemented was one of OCB, emotional intelligence, job satisfaction and transformational leadership. Hypothesis testing was performed by implementing a multiple linear regression analysis. The results of the data analysis toward 146 respondents stated that variables of emotional intelligence, job satisfaction and transformational leadership altogether predicted the nursesâ OCB (F = 16,062, p< 0,05) with a contribution for about 24,4%. Key words: Organizational citizenship behavior, emotional intelligence, job satisfaction, transformational leadership